Application of cooperative learning type Quick on the Draw on buffer solution material to improve learning outcomes of Class XI students - Rudi, La; Widiyanto, Brian Tri; Saefuddin, Saefuddin; Esnawi, Esnawi (Universitas Lampung, 2023)
This research aims to determine student learning outcomes, determine effectiveness and determine student responses to the quick on the draw type cooperative learning model on buffer solution material. The sample of this research was class XI MIPA 3 students using simple random sampling. The method used is quasi-experimental with a Randomized Control Group Pretest-Posttest Design. From the research results, it was found that the learning outcomes of students who were taught using the quick on the draw type cooperative learning model on buffer solution material were obtained on average 79.68 while the control class was 77.42 with completeness of learning outcomes based on the KKM score of 83.9% for the experimental and 61.74% for the control class. Based on the analysis of the N-gain value, it was found that the quick on the draw learning model was effective for use in buffer solution material, this was because the N-gain value for the experimental class reached the high category of 35% while the control class was 19%. The results of the analysis of student response questionnaires showed that 68% of students said they were very interested in the quick on the draw learning model because learning was more fun, and 87% of students were very motivated in learning. DOI: 10.23960/jppk.v12.i3.23.11